2001
DOI: 10.1073/pnas.012363899
|View full text |Cite
|
Sign up to set email alerts
|

Hpt, a bacterial homolog of the microsomal glucose- 6-phosphate translocase, mediates rapid intracellular proliferation inListeria

Abstract: Efficient replication in vivo is essential for a microparasite to colonize its host and the understanding of the molecular mechanisms by which microbial pathogens grow within host tissues can lead to the discovery of novel therapies to treat infection. Here we present evidence that the foodborne bacterial pathogen Listeria monocytogenes, a facultative intracellular parasite, exploits hexose phosphates (HP) from the host cell as a source of carbon and energy to fuel fast intracellular growth. HP uptake is media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
196
1
8

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 234 publications
(210 citation statements)
references
References 43 publications
5
196
1
8
Order By: Relevance
“…These permeases belong to the organophosphate:inorganic phosphate antiporter family of the major facilitator superfamily of permeases (114). It has been shown that the permeases from Chlamydiaceae are closer to the mammalian permeases on a protein tree than they are to other bacterial hexose-P permeases (26), and lateral gene transfer (LGT) in one direction or the other was suggested. Since that time, the genome of "Ca.…”
Section: Impact Of Trp Limitation On Carbon Sourcementioning
confidence: 99%
“…These permeases belong to the organophosphate:inorganic phosphate antiporter family of the major facilitator superfamily of permeases (114). It has been shown that the permeases from Chlamydiaceae are closer to the mammalian permeases on a protein tree than they are to other bacterial hexose-P permeases (26), and lateral gene transfer (LGT) in one direction or the other was suggested. Since that time, the genome of "Ca.…”
Section: Impact Of Trp Limitation On Carbon Sourcementioning
confidence: 99%
“…This metabolic process depends on the synthesis of Hpt, a hexose phosphate transporter protein that enables bacterial intracellular multiplication and is necessary for proliferation in mouse organs. 145,146 The lipoate ligase LplA1 is among other bacterial proteins required for growth in host cells. This enzyme is essential to perform a critical lipoyl modification in the E2 subunit of pyruvate dehydrogenase, in the presence of limiting concentrations of available host lipoyl substrates, which suggests that abortive growth is due to loss of pyruvate dehydrogenase function.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…Listeriolysin O (LLO), a secreted pore-forming cytolysin, has specifically evolved for activity in a phagosome by having a low pH optimum (5). Two other virulence factors, a hexose phosphate transporter and a lipoate protein ligase, are specific adaptations for intracellular replication and survival (6,7). Here, we report that Listeria monocytogenes phosphatidylinositol-specific phospholipase C (LmPI-PLC) has also evolved for intracellular growth and virulence by a specific structural modification that leads to greatly reduced activity on glycosylphosphatidylinositol (GPI)-anchored proteins.…”
mentioning
confidence: 99%